The Representation of Body Image and Self-Acceptance of The Main Character in 45 Pounds (More or Less) By K.A Barson - Audina, Vicky Cecil; Kusumayanti, Dina Dyah; Supiastutik, Supiastutik (Universitas Pendidikan Indonesia, 2024)
This research is an analysis of the representation of body image and self-acceptance issues of the main character in 45 Pounds (More or Less) through the perspective of Hall’s representation theory. By applying Hall's theory of representation to this research, the researcher gains a deeper understanding of how the novel represents and reinforces cultural norms and values related to body image and self-acceptance, and how these representations shape the feelings and emotions of readers related to the discourse of body image and self-acceptance.This study uses a qualitative research method in which the data sources are primary and secondary data. The primary data are in the form of narrations, dialogues and statements in the novel by K.A Barson entitled 45 Pounds (More or Less) as the main focus in this research. The secondary data includes the historical data, psychological research and cultural studies on body image and self-acceptance. This research focuses on the representation of body image and self-acceptance issue and the critical position of the author through the sense or content in 45 Pounds (More or Less). The analysis results shows that these issues were predominantly influenced by the media’s portrayal of unrealistic beauty standards, leading characters to constantly compare themselves and feel dissatisfied. The author prioritized health over vanity and encouraged readers to look beyond societal pressures, promoting a deeper appreciation of one’s body and self-worth